A systematic review on the anthelmintic effects of milk - Hamdan F.; Addnan F.H.; Abdullah W.O.; Elkadi M.A.; Rauf A.N.A.; Nur Fariha Mohd Manzor; Khairun Nain Nor Aripin; Fadlul Azim Fauzi Mansur (American Scientific Publishers, 2024)
Indexed by SCOPUS